2013
DOI: 10.1095/biolreprod.112.105692
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Glucose Phosphate Isomerase by the 3′UTR-Specific miRNAs miR-302b and miR-17-5p in Chicken Primordial Germ Cells1

Abstract: Glucose phosphate isomerase (GPI) involves in the reversible isomerization of glucose-6-phosphate to fructose-6-phosphate in glucose pathways. Because glucose metabolism is crucial for the proliferation and differentiation of embryonic stem and germ cells, reducing GPI expression may affect the characteristic features of these cells. MicroRNAs (miRNAs) have been shown to regulate genes. In the present study, we investigated the regulation of chicken GPI by its predicted miRNAs. We determined the expression pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…miR-140-5p downregulated the expression of TGF-βII receptors, while miR-23b and let-7 g upregulated TGF-βII receptor activity (Yang, Fang, Chang, & Yang, 2013). The clinical data confirmed that miR-17-5p and miR-20 could also regulate the TGF-βII receptor to influence the HTS processes (Dews et al, 2010;Rengaraj et al, 2013). Alao, were also considered to influence TGF-β1 to regulate collagen synthesis (Ferrante et al, 2015;Zhou et al, 2017).…”
Section: Mirna Regulation Of Specific Target Genes or Proteinmentioning
confidence: 68%
“…miR-140-5p downregulated the expression of TGF-βII receptors, while miR-23b and let-7 g upregulated TGF-βII receptor activity (Yang, Fang, Chang, & Yang, 2013). The clinical data confirmed that miR-17-5p and miR-20 could also regulate the TGF-βII receptor to influence the HTS processes (Dews et al, 2010;Rengaraj et al, 2013). Alao, were also considered to influence TGF-β1 to regulate collagen synthesis (Ferrante et al, 2015;Zhou et al, 2017).…”
Section: Mirna Regulation Of Specific Target Genes or Proteinmentioning
confidence: 68%
“…Several studies have reported that the overexpression of miRNAs downregulates their target genes, while downregulation of miRNAs upregulates their target genes, owing to their post-transcriptional gene regulatory functions [7]. This hypothesis is somewhat supported in the case of gga-miR-9-5p, gga-miR-20b-5p, gga-miR-196-5p, and gga-let-7d and the expression of their target genes MAP3K3 , MAP3K2 , AQP4 , and IGF2BP3 , respectively in the IML of NE-induced M5.1 chickens.…”
Section: Resultsmentioning
confidence: 99%
“…The expression and/or regulation of miRNAs are crucial for various biological activities including cell proliferation and differentiation, embryo development, disease progression, and cellular metabolisms. Several studies have reported that miRNAs preferentially bind to the 3′-untranslated region (3′UTR) during post-transcriptional gene regulation [6,7]. miRNAs regulate genes in both normal and disease conditions; however, the expression of miRNAs itself altered in most cancer and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, what is even more interesting is that it has been also shown that these miRNAs regulate brain-derived neurotrophic factor (BDNF) [30][31][32]. Other miRNAs differentiating the SWR/J control from the WT control group of mice, such as miR-20 and miR-106, are associated with the regulation of glucose metabolism [33], whilst miR-93 and miR-106 might affect liver diseases [34]. Additionally, miR-106 has been linked with regulation of the MAPK signaling pathway during oxidative stress [35].…”
Section: Discussionmentioning
confidence: 99%